2014
DOI: 10.3390/polym6041074
|View full text |Cite
|
Sign up to set email alerts
|

Fed-Batch Control and Visualization of Monomer Sequences of Individual ICAR ATRP Gradient Copolymer Chains

Abstract: Based on kinetic Monte Carlo simulations of the monomer sequences of a representative number of copolymer chains (≈ 150,000), optimal synthesis procedures for linear gradient copolymers are proposed, using bulk Initiators for Continuous Activator Regeneration Atom Transfer Radical Polymerization (ICAR ATRP). Methyl methacrylate and n-butyl acrylate are considered as comonomers with CuBr 2 /PMDETA (N,N,N′,N′′,N′′-pentamethyldiethylenetriamine) as deactivator at 80 °C. The linear gradient quality is determined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 44 publications
0
63
0
1
Order By: Relevance
“…[58,[92][93][94][95][96][97][98][99][100][101] For example, Tobita [92] derived an analytical expression for the CLD for a simplified batch RAFT polymerization reaction scheme, considering only intrinsic and constant reaction probabilities and including an extension to describe the product properties for RAFT polymerizations in continuous stirred tank reactors. For more detailed RAFT polymerization kinetic models, the most important stochastic method is the kinetic Monte Carlo method, [93][94][95][96][97][98] following the algorithm as proposed by Gillespie. [99,100] A key aspect is the initial number of molecules, which needs to be sufficiently high in case a more detailed kinetic description is aimed at, involving the accurate calculation of the concentration of (nonabundant) radical species.…”
Section: Kinetic Modeling Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…[58,[92][93][94][95][96][97][98][99][100][101] For example, Tobita [92] derived an analytical expression for the CLD for a simplified batch RAFT polymerization reaction scheme, considering only intrinsic and constant reaction probabilities and including an extension to describe the product properties for RAFT polymerizations in continuous stirred tank reactors. For more detailed RAFT polymerization kinetic models, the most important stochastic method is the kinetic Monte Carlo method, [93][94][95][96][97][98] following the algorithm as proposed by Gillespie. [99,100] A key aspect is the initial number of molecules, which needs to be sufficiently high in case a more detailed kinetic description is aimed at, involving the accurate calculation of the concentration of (nonabundant) radical species.…”
Section: Kinetic Modeling Techniquesmentioning
confidence: 99%
“…Finally, so-called hybrid methods [93][94][95]102] have also been developed which combine deterministic and stochastic elements. For example, Konkolowicz et al [103][104][105] have calculated the change of the RAFT polymerization CLD for a given time step by integrating moment equations and subsequent sampling of the polymeric reaction events to construct the CLD.…”
Section: Kinetic Modeling Techniquesmentioning
confidence: 99%
“…This optimization is performed at the maximal temperature of 90 °C, for illustration purposes only. Importantly, the term overall conversion (Xm,overall) needs to be introduced [32]. This conversion is defined with respect to the initial molar amount of monomer used in the batch reference case (nM,0,batch): (1) in which nM,reacted is the molar amount of monomer that has already reacted.…”
Section: Variation Of Monomermentioning
confidence: 99%
“…It has been indicated that the outcome of the ARGET ATRP is very sensitive to the initial concentrations. In particular, the amount of reducing agent has to be selected carefully, taking into account a trade-off between polymerization rate and livingness [29][30][31][32]. Moreover, by switching to continuous operation, a more industrial attractive process can be obtained [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…[103] Operationally, the simplest way to produce an asymmetric copolymer with any desired composition profile is to add both monomers simultaneously under starved-feed conditions. [131] In this case, the monomer concentration in the reactor is very low throughout the polymerization, and the copolymer composition will always closely approximate the monomer feed. However, as propagation is limited by the low monomer concentration, higher incidence of side reactions is expected compared to batch polymerization.…”
Section: Forced Methodsmentioning
confidence: 99%